IMPLEMENTASI PROGRAM EAARTH HOUR IN KOTA PEKANBARU - Pangestu, Indri Yulia; Rani, Faisyal (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This paper is a contemporary study that provides knowledge about the implementation of an international organization program in Pekanbaru, namely the Earth Hour program.This paper uses a conceptual foundation, by implementing the role of program implementation to see how big the implementation of the Earth Hour program is by focusing on specific areas. Supported by the theory of the role of international organizations, pluralist perspectives and the analysis of international organizations, as well as the concept of Environmentalism.Some implementations of the World Wide Found for Nature (WWF) in the Earth Hour Pekanbaru program are Advocacy strategies, Lobbying strategies, Networking Strategies, Visibility Strategies, Planning Strategies for Public Relations Campaigns, Crowdfunding and Crowdsourcing Strategies and communication strategies for environmental pollution campaigns in Pekanbaru City . So far these efforts have produced good results for the awareness of Pekanbaru City Government and the community to change good behavior towards the environment.Keywords: International Organization, World Wide Found for Nature (WWF) WWF, Earth Hour